Comparison of Complications after Primary and Secondary Anterior Chamber Intraocular Lens Implantation - Arshad Shaikh, M.S. Fahmi, Uzma Fasih, Ishtiaque Ahmed (Pakistan Journal of Ophthalmology, 2010)
Purpose: To assess and compare the complications of primary and secondary implantation of flexible open loop anterior chamber intraocular lenses. Materials and Methods: The study was conducted in the Department of Ophthalmology, Abbasi Shaheed Hospital from January 2007-June 2008. In this study evaluation of 60 patients with flexible open loop AC IOLs were divided into equal groups. .In group l (n=30) an AC IOL was implanted primarily and in group ll (n=30) secondary implantation was done after two months of complicated ECCE. Follow up period was from 1 to 8 weeks. The best corrected visual acuity and complications within two months were obtained. Result: Mean post operative best corrected visual acuity in group l was lower than group ll .Best corrected visual acuity of 6/18 or better was achieved in 13 of 30 in group l and 19 of 30 in group ll. The difference was not statistically significant (p>0.05) Post operative complications were significantly lower in group ll (p<0.05). In group l 30 eyes had a total of 92 complications while 30 eyes had 58 complications in group ll. Conclusion: Flexible open loop AC IOLs are suitable for both primary and secondary implantations to correct aphakia .Secondary implantation of flexible open loop AC IOLs after complicated ECCE seems to have more favourable visual outcomes and a lower complications rate than primary implantations in complicated ECCE cases.